Notes on Diffraction: Gabriel Orozco and Photography. - Grace, Claire (Art Journal)
The author discusses the science of diffraction and how it relates to Gabriel Orozco's documentary photography. Topics explored include the possible application of diffraction on various wave systems such as water and light, the tension between dimensions presented by Orozco in his 1992 photograph "Extension of Reflection," and observations on the composition and physics of his 1993 photograph "From Roof to Roof."